2023
DOI: 10.3390/app13127206
|View full text |Cite
|
Sign up to set email alerts
|

SAFEPA: An Expandable Multi-Pose Facial Expressions Pain Assessment Method

Abstract: Accurately assessing the intensity of pain from facial expressions captured in videos is crucial for effective pain management and critical for a wide range of healthcare applications. However, in uncontrolled environments, detecting facial expressions from full left and right profiles remains a significant challenge, and even the most advanced models for recognizing pain levels based on facial expressions can suffer from declining performance. In this study, we present a novel model designed to overcome the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
(119 reference statements)
0
0
0
Order By: Relevance
“…The availability of many face images and/or video datasets for pain assessment has driven recent advances in the field of automatic pain assessment. The UNBC-McMaster Shoulder Pain Expression Archive Database (UNBC-McMaster) [44] is the one of the most widely utilized of these datasets [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][17][18][19][20][21]. This dataset was gathered from 25 adult participants suffering from shoulder pain, which form 48,398 RGB frames issued from 200 variable-length videos (see details in Table 1).…”
Section: Publicly Accessible Pain Assessment Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…The availability of many face images and/or video datasets for pain assessment has driven recent advances in the field of automatic pain assessment. The UNBC-McMaster Shoulder Pain Expression Archive Database (UNBC-McMaster) [44] is the one of the most widely utilized of these datasets [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][17][18][19][20][21]. This dataset was gathered from 25 adult participants suffering from shoulder pain, which form 48,398 RGB frames issued from 200 variable-length videos (see details in Table 1).…”
Section: Publicly Accessible Pain Assessment Datasetsmentioning
confidence: 99%
“…As a result, the UNBC-McMaster dataset size was reduced from 48,398 frames to 10,783 frames. Furthermore, another well-used dataset [6,8,20,45,59] is the BioVid Heat Pain dataset [45,59], which was formed by collecting 17300 RGB videos from 87 subjects of 5 s each with a frame rate of 25 fps. An inducted heat pain was the cause of the pain represented in these videos.…”
Section: Publicly Accessible Pain Assessment Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments concluded that the implementation of facial recognition as part of ERS towards video surveillance system can improve the reliability of abnormal behavior detection via facial expressions depending on different emotions and environmental conditions. Furthermore, facial expressions can be used in identifying pain, which will benefit the healthcare industry [39]. Assessing a patient's pain levels over time is deemed to be important, specifically regarding the effectiveness of medical treatments.…”
Section: Ers Applicationsmentioning
confidence: 99%
“…Previous investigations have demonstrated that facial action units (AUs) may be detected for autonomous pain expression evaluation (Alghamdi and Alaghband, 2023). On the contrary, existing methods for identifying facial pain AUs are restricted to regulated circumstances.…”
Section: Introductionmentioning
confidence: 99%